2021
DOI: 10.3390/ijerph18031322
|View full text |Cite
|
Sign up to set email alerts
|

Could Emotional Intelligence Ability Predict Salary? A Cross-Sectional Study in a Multioccupational Sample

Abstract: The study of emotional intelligence (EI) in work environments is a trending topic. However, few studies have examined the relationship between EI and salary. Therefore, the presented research aims to analyze the influence of EI on salary using a multioccupational sample. The participants were 785 subjects aged between 18 and 58 years (M = 39.41; SD = 10.95). EI ability was measured using the Mobile Emotional Intelligence Test (MEIT), while the salary was collected together with other sociodemographic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…After all, the public health response to the pandemic should not only reduce uncertainty by clear, concise and accurate data about measures, infection and death rates but also turn this crisis into an opportunity for improvement in mental health knowledge, which when extrapolated into any professional category help individuals face both tough circumstances and different types of people that at the end merely hinge on our capacity of effective management of emotions as part of our work aiming professional success ( Moreno et al, 2020 ; Sanchez-Gomez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After all, the public health response to the pandemic should not only reduce uncertainty by clear, concise and accurate data about measures, infection and death rates but also turn this crisis into an opportunity for improvement in mental health knowledge, which when extrapolated into any professional category help individuals face both tough circumstances and different types of people that at the end merely hinge on our capacity of effective management of emotions as part of our work aiming professional success ( Moreno et al, 2020 ; Sanchez-Gomez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017). Employees with higher emotional intelligence are observed to have higher salaries (Sanchez-Gomez et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Emotional intelligence was also expressed as a solid forecaster for employees' satisfaction. Gomez (2020Gomez ( , 2021 concluded that professionals who presented with higher levels and components of EI had best job performance. In order to achieve high professional efficacy, the impact of emotional intelligence cannot be ignored.…”
Section: Literature Reviewmentioning
confidence: 99%